2017
DOI: 10.1002/2017jc013111
|View full text |Cite
|
Sign up to set email alerts
|

Front‐Eddy Influence on Water Column Properties, Phytoplankton Community Structure, and Cross‐Shelf Exchange of Diatom Taxa in the Shelf‐Slope Area off Concepción (∼36–37°S)

Abstract: In eastern boundary current systems (EBCSs), submesoscale to mesocale variability contributes to cross‐shore exchanges of water properties, nutrients, and plankton. Data from a short‐term summer survey and satellite time series (January–February 2014) were used to characterize submesoscale variability in oceanographic conditions and phytoplankton distribution across the coastal upwelling and coastal transition zones north of Punta Lavapié, and to explore cross‐shelf exchanges of diatom taxa. A thermohaline fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 104 publications
(179 reference statements)
1
31
0
Order By: Relevance
“…The first one is that the satellite-derived spatial distribution of the PSC in CZ and CTZ in the study region is consistent with previous reports using in situ data from the same region; that is, nanoplankton dominates in the CTZ, whereas microplankton does so in the CZ, e.g., [30,60,81,84]. The second one is that previous in situ studies on PSC associated with mesoscale eddies have shown that an important fraction of the coastal microplankton in this region appears to be advected by these features during their early stages of development [32,33].…”
Section: Application Of a Three-component Abundance-based Model To Resupporting
confidence: 80%
See 4 more Smart Citations
“…The first one is that the satellite-derived spatial distribution of the PSC in CZ and CTZ in the study region is consistent with previous reports using in situ data from the same region; that is, nanoplankton dominates in the CTZ, whereas microplankton does so in the CZ, e.g., [30,60,81,84]. The second one is that previous in situ studies on PSC associated with mesoscale eddies have shown that an important fraction of the coastal microplankton in this region appears to be advected by these features during their early stages of development [32,33].…”
Section: Application Of a Three-component Abundance-based Model To Resupporting
confidence: 80%
“…In the region off central-southern Chile, waters with high nitrate and silicate concentrations (~10 µM) have been associated with the upwelling of the Equatorial Subsurface Waters (ESSW) in the CZ, favoring the dominance of the microplankton fraction (e.g., diatoms) [85,86]. In contrast, waters in the CTZ are often lower in silicate concentration leading to changes in the nitrate:silicate ratios [33]. Ratios close to 1:1 have favored the growth of large phytoplankton cells, whilst higher values (>3:1) can produce shifts in the size of diatoms and/or changes towards other small functional groups [33,87,88].…”
Section: Shifts On Phytoplankton Size Classes Within Mesoscale Eddiesmentioning
confidence: 99%
See 3 more Smart Citations